The Persian Gulf War and the new international order: the end of Cold War and its impact - Arias Quincot, César (Universidad del Pacífico, 1990)
​The author analyzes the international context in which the Persian Gulf War occurred. He points out that it was the first military conflict of importance that happened in the new international order that has arisen after the end of the hegemony of one superpower, hegemony that has replaced the bipolarity arisen after World War II. This fact explains the way in which the conflict was solved.